Pemberdayaan Masyarakat Melalui Penyuluhan Manfaat Rebusan Air Daun Sirih Terhadap Fluor Albus di Vagina Pada Wanita Usia Reproduktif di Kelurahan Ladang Bambu Tahun 2023 - Arva Rochmawati; Sari Rahma (Indonesian Journal Publisher, 2023)
Women have many problems in the vaginal area. Most cases that occur are vaginal discharge. Vaginal discharge or in medical language called flour albus is excessive discharge from the vagina that is not menstrual blood. Non-pharmacological treatment of vaginal discharge can be done by changing personal hygiene behavior, psychology, and using betel leaves. Betel leaf has been scientifically proven to inhibit the growth of Candida albicans at various concentrations (20-100%). Based on data obtained in Ladang Bambu Village on August 10, 2023, there were 12 women of reproductive age who experienced vaginal discharge, with an average age of 21-36 years, The average age of 21-36 years, women of reproductive age in Ladang Bambu Village have never known the many benefits of green betel leaves, so the community service team is interested in conducting Health Education in the form of counseling related to the benefits of betel leaf cooking water against fluor albus in women of reproductive age in Ladang Bambu Village.